INOVASI PERMAINAN TEBAK BUNYI MELALUI MEDIA AUDIO-VISUAL UNTUK MENINGKATKAN KEMAMPUAN KOGNITIF ANAK USIA 5-6 TAHUN DI R.A AL-AMIN MEDAN - Siti Mayam Lubis; Darajat Rangkuti; Darmina Eka Sari Rangkuti (Program Studi PG-PAUD Universitas PGRI Adi Buana Surabaya, 2022)
In the learning process, teachers rarely use guessing games, so that most children have not been able to develop their cognitive abilities properly. Audio-visual media is a medium that can stimulate the development of children's cognitive abilities, so that children are able to name objects based on color and shape, and classify objects based on color and shape. This study aims to determine the effect of playing charades using audio-visual media on group B children at RA Al Amin. This type of research is quantitative-experimental, consisting of 8 meetings. The data collection instrument was an informal test consisting of a pretest and posttest. The data obtained were analyzed by means of quantitative-descriptive analysis. The results of the normality test stated that the pretest and posttest data came from populations that were normally distributed. While the results of testing the hypothesis stated that tcount (3.74) > ttable (1.74), so it was concluded that there was an effect of playing guessing or sound on the cognitive ability to recognize numbers in group B children at RA Al Amin.